President of Ukraine: development of his legal status and constitutional fixing of term of his appointments - Кохановський, В. В. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
Analysis of the formation of the Institute of Presidency in Ukraine, worked out by the foreign experienceof the election and the strengthening of the authority of Heads of State, for the need at the constitutionallevel, clearly and unequivocally to the time of the next presidential election.